FORMULASI KEBIJAKAN SEKTOR PARIWISATA: PEMBERDAYAAN DAN PENINGKATAN PEREKONOMIAN PELAKU USAHA - Asriati, Asriati; Wardhana Mamonto, Moch Andry Wikra; Ramadani, Rizki; Suryani, St. (Universitas Ekasakti, 2023)
One of the authorities of the Regional Government is the field of tourism, this delegation of authority is emphasized in several laws and regulations. However, North Toraja Regency, which has tourism potential, does not yet have derivative regulations to empower and improve the economy of business actors. This article focuses on disclosing the basis for the formation of local regulations on the implementation of tourism and content specifically related to business actors. The method used is normative-empirical, focusing on examining primary data through open interviews, and examining secondary data, analyzed qualitatively. Referring to several laws and regulations, it is regulated that the local government has the authority and even emphasized several obligations to take care of tourism affairs, so that the North Toraja Regency government is seen as important to form regional regulations, while the content material related to business actors is realized by setting the norms of obligation for the government to conduct training for business actors, where the material is prepared on the basis of research so that business actors in the tourism and culinary management sector are able to increase the number of tourists, the income of business actors, as well as regional original income, the article contains standardization of the construction of identical infrastructure for each regions, and facilitating special partnerships with the need for appropriate technology for business actors, as well as facilitating access to capital with banks and investors.